Hubungan Antara Tingkat Pengetahuan Mengenai Antibiotik Dan Penggunaanantibiotik Tanpa Resep Dokter Pada Pelajar Kelas X, XI, XII Di SMK Negeri 2 Surakarta - Putri Anjany, Kiky; , dr. Sri Wahyu Basuki M.Kes; , ni Triastuti M.Ed. Ed (2016)
Background: Antibiotics is a very well known drug and widely used by the public, that can occure antibiotics abuse in society. The most action of antibiotics abuse in society consist of student self-treatment (swamedikasi) without doctor prescription. Antibiotics usage without doctor prescription will impact the incidence of antibiotics resistance and irrational usage of antibiotics. Purpose: This aim of study was to investigate the relationship between the levels of knowledge about antibiotics and antibiotics usage without doctor prescription to the student in class Xth, XIth and XIIth of SMK Negeri 2 Surakarta. Methods: This study was an observational analytic with cross sectional approach. The selection of sample with a cluster random sampling method obtained 90 respondens from class Xth, XIth and XIIth of SMK Negeri 2 Surakarta. Result: The result of Chi-Square test showed a significant correlation between the level of knowledge about antibiotics and antibiotics usage without doctor prescription to the student in class Xth, XIth and XIIth of SMK Negeri 2 Surakarta with p score p=0,004 (p<0,05) Conclusions: There is a significant relationship between the level of knowledge about antibiotics and antibiotics usage without doctor prescription to the students in class Xth, XIth and XIIth of SMK Negeri 2 Surakarta.